HUBUNGAN PENGETAHUAN GIZI, BESAR UANG SAKU, DAN KEBIASAAN KONSUMSI JAJANAN TERHADAP STATUS GIZI LEBIH PADA REMAJA DI SMAN 80 JAKARTA - Atika Rachmayanti, (2023)
Background: Overnutrition in adolescents continues to increase every year, adolescents with overnutrition are at risk of obesity and degenerative diseases, as well as worsening the state of the disease experienced. In Indonesia, the prevalence of overnutrition in adolescents aged 16-18 years in 2018 was 13.5%, while in DKI Jakarta province, the prevalence reached 21.1%. The purpose of this study was to determine the relationship of nutritional knowledge, pocket money, and snacks consumption habits to overweight status in adolescents at SMAN 80 Jakarta. Methods: This study was an analytic observational study using a cross sectional design. The sample of this study were X and XI grade students of SMA Negeri 80 Jakarta as many as 73 respondents using stratified random sampling technique. Data analysis in this study used the Chi-Square statistical test. Results: Based on the results of bivariate data analysis, it shows that there is no significant relationship between nutritional knowledge (p = 0.332), pocket money (p = 1,000), and snacks consumption habits (p = 1,000) on nutritional status in adolescents at SMAN 80 Jakarta. Conclusion: There is no significant relationship between nutritional knowledge, pocket money, and snacks consumption habits on the nutritional status of adolescents at SMAN 80 Jakarta.